Teachers’ common approaches in teaching literature by using cognitive approach in secondary schools, Malaysia - Abdullah, Suhaila; Idrus, Faizah; Sheikh Ahmad, Ismail (Research and Innovation Management Centre (RMC), International Islamic University College Selangor (KUIS), 2023)
This qualitative research studies teachers’ common approaches used for teaching literature for the past two years (2020-2022) and this research is part of an ongoing study to explore whether they could incorporate cognitive poetics in the teaching of literature in the classroom. The use of cognitive poetics in teaching literature in the classroom is the main area that is studied in this research and the researchers intend to find out if this approach could assist teachers in teaching this subject to facilitate students’ understanding of literary texts. This paper would like to shed findings on the common approaches that teachers used to garner students’ interests in studying literary works. The implication of this research is to answer the questions whether the common approaches used by the teachers lead to the declining interest in the subject among students.